A Redox Chemistry-based Function for Parkinson Disease-linked Parkin Confers Direct, Anti-oxidant Activities in Mammalian Brain - El Kodsi, Daniel N. (Université d'Ottawa / University of Ottawa, 2020)
Early-onset Parkinson disease, of which the best studied and most common cause are biallelic mutations in the PRKN gene, is characterized by an age of onset before 40 years. Parkin-deficient patients show slow progression, excellent responsiveness to L-dopa therapy, and are generally spared cognitive decline. At autopsy, PRKN-linked Parkinson disease is further distinguished by relative selectivity in cell loss, namely of dopamine producing neurons in the human brainstem, and the general absence of Lewy body inclusions. Since its discovery two decades ago, the field has focused on the function of parkin as an E3 ubiquitin ligase and its related role in mitophagy. However, its essential, neuroprotective function in ageing human midbrain and the mechanisms by which wildtype parkin preserves dopamine cell health in aged humans are yet to be elucidated. I hypothesized that parkin confers neuroprotection due to a redox function by its many cysteines (7.5%). We first focused on parkin’s biochemistry, reporting a shift from solubility to a nearly insoluble, aggregated state in adult control brain after age 40 years. We detected cysteine-based, post-translational modifications of parkin in response to oxidative stress, and characterized a novel, redox chemistry-based function: Through its own oxidation parkin reduced hydrogen peroxide in vitro. I validated this finding by showing its elevation in parkin-deficient, human brain. Wild-type parkin also participated in dopamine metabolism through the conjugation of reactive radicals at several of its cysteines, which augmented the generation of melanin. (Chapter 2). In addition, we demonstrated parkin’s heretofore unknown, antioxidant function in the cytosol using cellular paradigms and select genetic as well as toxin-based mouse models that featured elevated oxidative stress. Moreover, we uncovered parkin’s contribution to the wider thiol network, namely through an apparent feedback loop with glutathione metabolism (Chapter 3). Lastly, I developed and investigated a bi-genic (prkn-/-//Sod2+/-) model in an attempt to restage the pathogenesis of early-onset parkinsonism in mice; there, we detected a rise in systemic, oxidative stress and in total nitrotyrosination profiles of the brain, but did not observe any dopamine neuron loss in the midbrain. In accordance, the behavioural characterization of these animals did not reveal any motor abnormalities (Chapter 4). Based on this previously unknown function for parkin in redox biology, I envision three future research directions: a) additional studies to delineate the full range of oxidative modifications of parkin versus neutralization of radicals; this, to better define the distinct pathogenesis of parkin-linked Parkinson’s when compared to other forms of the disorder; b) structural studies of its oxidative modifications in vitro and renewed attempts of staging parkin-linked dopamine cell death in vivo; and c) and importantly, the exploration of cause-directed therapy based on parkin’s redox functions to preserve dopamine neurons of the human midbrain throughout adulthood.
Keywords: Neuroscience; Parkinson disease; Parkin protein; Redox chemistry